The Importance of the Historical Method in the Field of Sociology: Values System in the Manuscript of the Mallorca History as a Model - Benharzallah, Mourad (جامعة الجيلالي ليابس سيدي بلعباس - مخبر البحوث والدراسات الاستشراقية فى حضارة المغرب الإٍسلامى, 2021)
This article provides a new reading of the reasons for the victory of the Christian forces and the defeat of the Muslims in the island of Mallorca through a historical method in the field of sociology that sheds light on the value system prevailing in the city of Mallorca, mainly social and religious values, before its fall. By relying on the manuscript of the History of Mallorca by Ibn Amira as a reference to document facts historical and social values related to the above in Mallorca society. The article also explains the relationship between sociology and history and the importance of historical analysis in studying the events, processes, and institutions of past civilizations to find the origins or precedents of contemporary social life and understand its nature and functioning. The article concludes with the importance of institutions in society in shaping the value system in a way that improves contemporary social life.
يقدم هذا المقال قراءة جديدة لأسباب انتصار القوى المسيحية وهزيمة المسلمين في جزيرة مايوركا من خلال منهج تاريخي في مجال علم الاجتماع. كما يلقي الضوء على منظومة القيم السائدة في مدينة مايوركا، والقيم الاجتماعية والدينية بشكل رئيسي، قبل سقوطها. بالاعتماد على مخطوطة تاريخ مايوركا لابن أميرة كمرجع لتوثيق الحقائق والقيم التاريخية والاجتماعية المتعلقة بما ورد أعلاه في مجتمع مايوركا. تشرح المقالة أيضًا العلاقة بين علم الاجتماع والتاريخ وأهمية التحليل التاريخي في دراسة أحداث وعمليات ومؤسسات الحضارات السابقة للعثور على أصول أو سوابق الحياة الاجتماعية المعاصرة وفهم طبيعتها وعملها. ويختتم المقال بأهمية المؤسسات في المجتمع في تشكيل منظومة القيم بطريقة تحسن الحياة الاجتماعية المعاصرة.
Keywords: الحضارات القديمة -- الحياة الاجتماعية -- القيم التاريخية